Detection of atmospheric pressure plasma-induced removal of fingerprints via analysis of histograms obtained by imaging ellipsometry. (13th April 2021) - Koulouris, N A; Tasche, D; Scheglov, A; Mrotzek, J; Gerhard, C; Viöl, W
Abstract: In this publication we report on the suitability of imaging ellipsometry for the semi-quantitative investigation of a contactless removal of human fingerprints from surfaces by an atmospheric pressure plasma tretament. Special attention is paid to the impact of the applied plasma on the complex mixture of biological substances of a fingerprint. For this purpose, the cleaning effect of an argon plasma at two different electrical powers is investigated. By using imaging ellipsometry as a analysis method it could be shown that the cleaning efficiency increases with increasing electrical power and plasma treatment time. In addition, measurements were made by means of x-ray photoelectron spectroscopy (XPS) in order to characterize the chemical composition of surface-adherent contamination and its plasma-induced modifications. It was found that especially the amount of organic impurities is reduced in the course of plasma treatment.